INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP RELIGIUS SISWA DI SMPN 13 MALANG - Arianti Ulan Husen; Nur Hasan; Imam Safi’i (VICRATINA, 2022)
The approach used in this study uses a qualitative research approach. The type of research used is the type of case study research. The purpose of this study was to describe how the internalization of Islamic religious education values in growing students' religious attitudes at SMPN 13 Malang. In this study, the researcher acts as an instrument as well as collects data. The results of the research that have been carried out are 1) The steps for internalizing the values of Islamic religious education in fostering students' religious attitudes are by submitting data according to facts, namely religious activities such as habituation of dhuha prayer in congregation in the morning, reciting activities, and religious lectures; 2) The process of internalizing the values of Islamic religious education in fostering students' religious attitudes through exemplary strategies, inculcating discipline, habituation methods, creating a religious environment; 3) The impact of internalizing the values of Islamic religious education in growing students' religious attitudes has positive and negative impacts